A Comprehensive Evaluation of Steroid Metabolism in Women with Intrahepatic Cholestasis of Pregnancy - Pařízek, Antonín; Hill, Martin; Dušková, Michaela; Vítek, Libor; Velíková, Marta; Kancheva, Radmila; Šimják, Patrik; Koucký, Michal; Kokrdová, Zuzana; Adamcová, Karolína; Černý, Andrej; Hájek, Zdeněk; et al. (PloS one, 2016)
Intrahepatic cholestasis of pregnancy (ICP) is a common liver disorder, mostly occurring in the third trimester. ICP is defined as an elevation of serum bile acids, typically accompanied by pruritus and elevated activities of liver aminotransferases. ICP is caused by impaired biliary lipid secretion, in which endogenous steroids may play a key role. Although ICP is benign for the pregnant woman, it may be harmful for the fetus. We evaluated the differences between maternal circulating steroids measured by RIA (17-hydroxypregnenolone and its sulfate, 17-hydroxyprogesterone, and cortisol) and GC-MS (additional steroids), hepatic aminotransferases and bilirubin in women with ICP (n = 15, total bile acids (TBA) >8 μM) and corresponding controls (n = 17). An age-adjusted linear model, receiver-operating characteristics (ROC), and multivariate regression (a method of orthogonal projections to latent structure, OPLS) were used for data evaluation. While aminotransferases, conjugates of pregnanediols, 17-hydroxypregnenolone and 5β-androstane-3α,17β-diol were higher in ICP patients, 20α-dihydropregnenolone, 16α-hydroxy-steroids, sulfated 17-oxo-C19-steroids, and 5β-reduced steroids were lower. The OPLS model including steroids measured by GC-MS and RIA showed 93.3% sensitivity and 100% specificity, while the model including steroids measured by GC-MS in a single sample aliquot showed 93.3% sensitivity and 94.1% specificity. A composite index including ratios of sulfated 3α/β-hydroxy-5α/β-androstane-17-ones to conjugated 5α/β-pregnane-3α/β, 20α-diols discriminated with 93.3% specificity and 81.3% sensitivity (ROC analysis). These new data demonstrating altered steroidogenesis in ICP patients offer more detailed pathophysiological insights into the role of steroids in the development of ICP.
Keywords: Steroids; intrahepatální cholestáza; komplikace těhotenství; ROC Curve; 17-alfa-hydroxypregnenolon; gestační stáří; 17-alpha-Hydroxyprogesterone; Liver Function Tests; Bile Acids and Salts; jaterní testy; Cholestasis, Intrahepatic; Gestational Age; Pregnancy; Dorsal Raphe Nucleus; těhotenství; plynová chromatografie s hmotnostně spektrometrickou detekcí; Adult; dospělí; Pregnancy Complications; radioimunoanalýza; 17-alfa-hydroxyprogesteron; hydrokortison; Alanine Transaminase; Hydrocortisone; Gas Chromatography-Mass Spectrometry; žlučové kyseliny a soli; plocha pod křivkou; Aspartate Aminotransferases; alanintransaminasa; nuclei raphe dorsalis; 17-alpha-Hydroxypregnenolone; lidé; ženské pohlaví; Radioimmunoassay; Humans; Area Under Curve; steroidy; aspartátaminotransferasy; Female; ROC křivka